Meaningful Synergy in E-learning Integrating Environmental Awareness and Project-Based Learning in EFL - Zunaidah, Asih (Academy of Education Journal, 2024)
The study investigates EFL e-learning project-based education and environmental awareness. Despite limited participation and technology concerns, e-learning is evolving. This study supports "green awareness" in higher education institutions, promotes environmental responsibility and global citizenship. Our study combines meaningful learning, project-based pedagogy, and online EFL instruction with active engagement. According to this study, project-based education and environmental awareness can boost EFL e-learning learners' involvement. These 300 university-level EFL students are being studied holistically with ADDIE. This comprises need analysis, design, material development, classroom implementation, and impact assessment. According to research, incorporating "green business" into online sessions increases student participation. A poll found that intervention promotes environmental consciousness. According to interviews, environmental awareness and sustainability motivate students to create environmentally responsible solutions. Despite limitations in depth and sample size, well-designed interventions increase online learning engagement. The findings contribute to more effective online education methods, instructional design, and student involvement investigations.